A semi-empirical model for mesospheric and stratospheric NOy produced by energetic particle precipitation - Funke, Bernd; López-Puertas, Manuel; Stiller, Gabriele P.; Versick, Stefan; Clarmann, Thomas (Atmospheric Chemistry and Physics, 2018)
The MIPAS Fourier transform spectrometer on board Envisat has measured global distributions of the six principal reactive nitrogen (NO y ) compounds (HNO 3 , NO 2 , NO, N 2 O 5 , ClONO 2 , and HNO 4 ) during 2002–2012. These observations were used previously to detect regular polar winter descent of reactive nitrogen produced by energetic particle precipitation (EPP) down to the lower stratosphere, often called the EPP indirect effect. It has further been shown that the observed fraction of NO y produced by EPP (EPP-NO y ) has a nearly linear relationship with the geomagnetic A p index when taking into account the time lag introduced by transport. Here we exploit these results in a semi-empirical model for computation of EPP-modulated NO y densities and wintertime downward fluxes through stratospheric and mesospheric pressure levels. Since the A p dependence of EPP-NO y is distorted during episodes of strong descent in Arctic winters associated with elevated stratopause events, a specific parameterization has been developed for these episodes. This model accurately reproduces the observations from MIPAS and is also consistent with estimates from other satellite instruments. Since stratospheric EPP-NO y depositions lead to changes in stratospheric ozone with possible implications for climate, the model presented here can be utilized in climate simulations without the need to incorporate many thermospheric and upper mesospheric processes. By employing historical geomagnetic indices, the model also allows for reconstruction of the EPP indirect effect since 1850. We found secular variations of solar cycle-averaged stratospheric EPP-NO y depositions on the order of 1 GM. In particular, we model a reduction of the EPP-NO y deposition rate during the last 3 decades, related to the coincident decline of geomagnetic activity that corresponds to 1.8 % of the NO y production rate by N 2 O oxidation. As the decline of the geomagnetic activity level is expected to continue in the coming decades, this is likely to affect the long-term NO y trend by counteracting the expected increase caused by growing N 2 O emissions.